Pengembangan E-Modul Interaktif pada Mata Pelajaran PAI Kelas VII di SMPN 3 Palopo - Yamin, Muhammad; Ismail, Ismail; Rodiyah, Siti (ISLAMIKA, 2025)
The creation of interactive e-modules for Islamic Religious Education and Character Education courses at SMPN 03 Palopo is covered in this paper. Determining the usefulness and relevance of the interactive e-module learning materials on the topic of presenting prayer and dhikr in life in class VII of Educating the First Nation 03 Palopo was the aim of this study. This study employs the ADDIE development paradigm and the R&D (Research and Development) research type. The study was conducted with 27 seventh-grade students from SMPN 03 Palopo during the 2024–2025 academic year. Data for this study was collected using practicality questionnaires, validation sheets, and interviews. The method of data analysis that was employed was In line with the study's quantitative descriptive analysis, the Interactive e-module of Islamic Religious Education and Character Education has satisfied the legitimate requirements in terms of validity, receiving scores of 80% from media experts, 94% from material experts, and 70% from language experts. Meanwhile, the practicality test through student responses, an arerage percentage of 83% was obtained, indicating that the interactive e-module media meets the criteria of being very practical.